Gut–Liver Axis: Liver Sinusoidal Endothelial Cells Function as the Hepatic Barrier in Colitis-Induced Liver Injury - Wang, Yang; Zhang, Yifan; Liu, Yun; Xu, Jun; Liu, Yulan (Frontiers in Cell and Developmental Biology, 2021)
Background: Based on the gut-liver-axis theory, a leaky gut can aggravate liver injury. However, clinical studies suggest that although gut mucosa damage is commonly observed in inflammatory bowel disease (IBD), it seldom leads to severe liver injury. We hypothesize that there is a hepatic barrier in the gut-liver-axis, which protects the liver against gut-derived invasive factors. Methods: Colitis was induced by dextran sulfate sodium (DSS) in 8 different liver injury models in Sprague-Dawley rats. Liver sinusoidal endothelial cells (LSECs) injury was evaluated by scanning and transmission electron microscope. Neutrophils were depleted by injection of anti-rat-polymorphonuclear serum. Two pneumonia models were also induced to investigate the mechanism of neutrophils recruitment and activation. LSECs isolated from rat liver were used to investigate the effect on the neutrophils recruitment and activation. Results: Among 8 liver injury models, DSS-colitis had no effect on liver injury in 3 models with normal LSECs. In the other 5 models with LSECs rupture, liver injury was significantly exacerbated by colitis, and increased hepatic neutrophils accumulation was observed. When neutrophils were depleted, colitis-induced liver injury was significantly attenuated. In pneumonia, liver injury and colitis models, the level of CXCL1 correlated with the recruitment of neutrophils in different tissues, while DSS-colitis and LSECs injury synergistically contributed to increased CXCL1 expression in the liver. In colitis-induced liver injury, neutrophils were activated in the liver. Injured LSECs showed both structural and functional changes, with significantly increased expression of CXCL1 and TNF-α under the stimulation of lipopolysaccharide (LPS). The combination of gut-derived LPS and LSEC-derived TNF-α led to the activation of neutrophils, characterized by enhanced production of reactive oxygen species, pro-inflammatory cytokines and the formation of neutrophil extracellular traps. Conclusion: LSECs constitute a vitally important barrier in the gut-liver-axis, defending the liver against colitis-induced injury. When LSECs are damaged, they can turn into a pro-inflammatory pattern under the stimulation of LPS. LSECs injury and colitis-derived LPS synergistically contribute to the recruitment and activation of hepatic neutrophils. Neutrophils play pivotal role as a downstream effector in colitis-induced liver injury.